Implementasi Norma Sosial dalam Memperkuat Hubungan Sekolah dan Masyarakat di SDN Surgi Mufti 4 - Dimas Saputra; Ahmadi Arfin; M. Maulana Syifa Russadi; Muhammad Hanafi; Muhammad Wildan Safitri; Muhammad Yusuf; Suhaimi Suhaimi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study explores how social norms can strengthen the relationship between schools and the community. It aims to analyze the implementation of social norms, identify supporting and inhibiting factors, and propose contextual solutions to improve collaboration. The research adopts a qualitative approach involving principals, teachers, educational staff, parents, community leaders, and local institutions over a period of three to four months. Data were collected through interviews, observations, and document analysis, and analyzed thematically. The findings reveal that schools that encourage two-way communication, actively involve the community in collaborative activities, and integrate social norms into leadership practices tend to build stronger and more sustainable relationships. Values such as mutual respect, openness, and shared responsibility play a key role in increasing community engagement, trust, and collective agreement. Overall, the study highlights that the effective implementation of social norms not only enhances collaboration but also contributes to improving educational quality and strengthening social connections between schools and the community.